Enough is Enough: De-colonise, Diversify and De-construct the Curriculum. Issue 1 (4th January 2022) - Housee, Shirin
Abstract : This article explores the importance of anti-racism in a higher Education context. With reference to the recent discussions on de-colonising the curriculum, I reflect on the importance of the Black Lives Matter movement. I argue more vehemently than ever before – enough is enough – we have no choice but to teach against racism. This article discusses the importance of de-colonising the curriculum and Higher Education and creating learning environments that open out discussions about everyday racism. This, I argue, is core to our anti-racist practise if we intend to build a fairer and a more anti-racist world.